MICROPROPAGATION OF A MEDICINAL PLANT WITHANIA SOMNIFERA L. DUNAL BY SHOOT BUD CULTURE - P. SONI; A. N. BAHADUR; U. TIWARI; V. K. KANUNGO (The Bioscan, 2011)
An efficient protocol was devised for rapid in vitro propagation of Withania somnifera through shoot bud culture. The proliferating auxiliary shoot was isolated from nodal explants of field grown Withania somnifera. established on Murashige and Skoogs medium (MS) and Gamborg B5 medium supplemented with six concentrations of Benzyl amino purine (BAP), Naphthalene acetic acid (NAA), Kinetin(Kn) and 2,4- Dichlorophenoxy acetic acid (2, 4-D). After 30 days of culture of Withania somnifera, the maximum numbers of shoots was produced on MS medium supplemented with 1.0mg/L BAP. Each of the explants had developed more than two shoots per nodes, while in six concentrations each of kinetin, NAA and 2, 4-D developed either two or less than two shoots/explants. The study revealed highest frequency of shoot formation and maximum number of shoots per explants in MS medium supplemented with 1mg/L BAP than the other growth hormone. Key Words: In vitro culture, Withania somnifera, multiple shoot induction.